2021
DOI: 10.1177/10820132211003705
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the type of packaging on the shelf life of ground rabbit meat

Abstract: Rabbit meat consumption has increased worldwide due to its health benefits in humans but few studies addressed the stability of this food matrix. The effect of two types of packaging (vacuum, VP; and polystyrene tray overwrap with PVC/polyvinyl plastic film, PT) was evaluated on the microbial stability (psychrotrophic; PSY, lactic acid bacteria; LAB, initial coliforms counts) and physicochemical (pH, thiobarbituric acid reactive substances (TBARS), total volatile basic Nitrogen (TBV-N), color and drip loss) ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Previous studies have investigated the microbiological quality of MAP meat products with natural plant additives, including sheep burgers [ 52 ], deer burgers [ 49 ] and beef burger patties [ 87 ], but not rabbit burgers. The effect of different types of packaging on the microbiological quality of rabbit meat has been studied [ 88 ], but MAP rabbit meat with the addition of garlic has not been analyzed to date.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the microbiological quality of MAP meat products with natural plant additives, including sheep burgers [ 52 ], deer burgers [ 49 ] and beef burger patties [ 87 ], but not rabbit burgers. The effect of different types of packaging on the microbiological quality of rabbit meat has been studied [ 88 ], but MAP rabbit meat with the addition of garlic has not been analyzed to date.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained here suggest that the marination process with incorporation of Ras El-Hanout combined with low-O 2 packaging was the most antimicrobial treatment in rabbit meat against the main spoilage microorganisms as compared to control samples. Wang et al [28] and Redondo-Solano et al [57] found that the TVBN content steadily increased during the retail display of rabbit meat. The Egyptian Organization for Standardization and Quality Control (EOS 1090/2005) has set guidelines and thresholds to define the freshness or spoilage of rabbit meat.…”
Section: Total Volatile Basic Nitrogen Of Rabbit Meatmentioning
confidence: 98%
“…For its part, this reduction can be at the origin of the oxidation of the pigment Mb [28,56]. Recently, Redondo-Solano et al [57] found that the color stability of stored ground rabbit meat was improved using vacuum storage compared to simple overwrapping. In light of our results, we can conclude that rabbit meat discoloration during exposure was significantly (p < 0.05) influenced by microbial spoilage, lipid oxidation, and possibly to a large extent by Mb oxidation.…”
Section: Color Stability Of Rabbit Meatmentioning
confidence: 99%
“…The provision of animal welfare and sustainability of RM producers and slaughterhouses also depends on state regulation in the form of the development of standards in the field of regulatory and technical support for the breeding and processing of rabbits, as well as the standardization of animal welfare assessment processes. Compliance of RM production with environmental principles can also be achieved only with the joint efforts of the state and the main market players associated with rational (waste-free) rabbit processing technology or optimization of waste management processes [ 16 ], as well as the use of sustainable packaging [ 144 , 145 ].…”
Section: Strategies For Sustainable Rabbit Meat Productionmentioning
confidence: 99%